Reference values of liver volume in Caucasian population and factors influencing liver size. Issue 106 (September 2018) - Kromrey, M.L.; Ittermann, T.; vWahsen, C.; Plodeck, V.; Seppelt, D.; Hoffmann, R.T.; Heiss, P.; Kühn, J.P.
Highlights: Liver volume is affected by age, gender, body mass index, and alcohol consumption. Parenchymal liver diseases, like fibrosis/cirrhosis, fatty liver disease, hepatic iron overload influence size of the liver. Reference values were established to aid in the diagnosis of parenchymal liver diseases. Abstract: Purpose: To investigate factors influencing liver size and to determine reference values of liver volume (LV) for healthy subjects. Methods: 2773 volunteers underwent magnetic resonance imaging (MRI) of the liver in the setting of the population based Study of Health in Pomerania. Based on measurement of maximum diameters in three orientations, LVs were calculated and correlated with demographic factors such as age, gender, and body mass index. In addition, LVs of healthy volunteers and participants with parenchymal liver diseases such as fatty liver disease, iron overload, fibrosis/cirrhosis were compared. Adjusted reference values of liver volumes were defined for the group of healthy participants. Results: In general, mean LV (mean ± standard deviation) was 1505 ± 385 cm 3 . Age, gender and body mass index correlated significantly with the liver volume (p ≤ 0.001). Parenchymal liver diseases significantly influence LV (with: 1624 ± 420 cm 3, n = 1525 and without parenchymal liver diseases: 1360 ± 273 cm 3 ; n = 1.248, p ≤ 0.001). Compared to LV of participants without liver diseases, LV was increased in volunteers with hepatic steatosis (1717 ± 419 cm 3 ; n = 1111), liver iron overload (1558 ± 367 cm 3 ; n = 553; p ≤ 0.001) as well as in participants with fibrosis/cirrhosis (1494 ± 459 cm 3 ; n = 383). Conclusions: LV is influenced by age, body mass index and parenchymal liver diseases. Reference values were established to aid in the diagnosis of parenchymal liver diseases.